Changes in Production Parameters, Egg Qualities, Fecal Volatile Fatty Acids, Nutrient Digestibility, and Plasma Parameters in Laying Hens Exposed to Ambient Temperature - Kim, Da-Hye; Lee, Yoo-Kyung; Lee, Sung-Dae; Kim, Sang-Ho; Lee, Sang-Rak; Lee, Hong-Gu; Lee, Kyung-Woo (Frontiers in Veterinary Science, 2020)
The present study was undertaken to investigate the impact of heat stress on nutrient digestibility and tibia and reproductive traits, and changes in laying performance, egg qualities, fecal volatile fatty acids, and plasma parameters in laying hens. One-hundred twenty 52-week-old laying hens were raised in three temperature-controlled facilities with constant humidity (50% RH), either normal temperature (LT; 22°C) or heat stress considered being moderate (MT; 27°C) or severe (HT; 32°C) for 42 days. Feed intakes were consistently low (p < 0.01) in HT hens compared with those in LT or MT over the period of 42 days. Egg production kept markedly (p < 0.05) or numerically (p > 0.05) low in hens exposed to HT vs. LT or MT. Egg mass and egg weight were consistently low (p < 0.01) in hens exposed to HT compared with those raised under LT or MT. On the other hand, feed conversion ratio and frequency of dirty and cracked eggs were not significantly affected (p > 0.05) during the experimental period. HT-exposed hens consistently had lowered (p < 0.05) eggshell thickness and breaking strength, eggshell weight, and plasma Ca, P, and Mg levels compared with LT- or MT-treated hens. HT hens had lower (p < 0.01) relative oviduct weight and less number of large yellow follicles compared with those raised under LT or MT conditions at 42 days. Tibia traits measured at 42 days were not affected by any of heat treatments. Fecal volatile fatty acids tended to be higher in HT-exposed laying hens throughout the experiment. It was noted that digestibilities of neutral detergent fiber and dry matter were lowest (p < 0.05) in hens exposed to HT vs. LT or MT environments. Our study suggests that heat stress could lower laying performance, egg quality, and physiological parameters that are coupled with alterations in gut metabolites and mineral/lipid metabolism. The findings emerged from this study will help us design the nutritional and environmental strategies to mitigate the negative effect of heat stress on laying hens.